PSILÍDEO DO CITROS (DIAPHORINA CITRI) - Venção Neto, Eduardo; De Carvalho, Tiago Rogério [UNESP]; Furlanetti, Alessandra Carla (Interface Tecnologica, 2025)
This work addresses the importance of the psyllid (Diaphorina citri) as a vector of the disease known as greening or Huanglongbing (HLB), which directly affects the world's citrus industry, causing major losses in quality and yield. This work aims to present the bioecological aspects of the insect, discussing its life cycle, behavior and adaptation in different environments. Furthermore, it analyzes the main control strategies used, from biological and chemical methods to integrated pest management, highlighting their limitations and recent advances. With this, we can conclude that although advances have been made in controlling the psyllid and mitigating greening, research and development of more efficient and sustainable management strategies is essential to effectively combat this pest, minimizing economic losses and protecting crops. citrus in the long term. Este trabalho aborda a importância do psilídeo (Diaphorina citri) como vetor da doença conhecida como greening ou Huanglongbing (HLB), que afeta diretamente a citricultura mundial, causando grandes perdas de qualidade e rendimento. Esse trabalho tem como objetivo apresentar os aspectos bioecológicos do inseto, discutindo seu ciclo de vida, comportamento e adaptação em diferentes ambientes. Além disso, analisa as principais estratégias de controle utilizadas, desde métodos biológicos e químicos até o manejo integrado de pragas, destacando suas limitações e avanços recentes. Com isso, podemos concluir que embora avanços tenham sido feitos no controle do psilídeo e na mitigação do greening, a pesquisa e desenvolvimento de estratégias de manejo mais eficientes e sustentáveis é essencial para o combate efetivo desta praga, minimizando os prejuízos econômicos e protegendo as culturas cítricas no longo prazo.
ameaça silenciosa aos pomares de citros e como controlá-la